Petrology and Tectonic Geophysics of Massive and Foliated Eclogites in the North Qilian Orogenic Belt: Changes in Mineral Composition, Oxygen Fugacity, and Fabric during Exhumation - Feng Wang; Daorong Zhou; Xunhua Zhang (Adsorption Science & Technology)
The North Qilian orogenic belt is a typical area of “cold” subduction of the early Paleozoic oceanic plate, forming a series of high pressure and low temperature metamorphic rock assemblages. Among them, eclogite is a kind of protolith, which is basaltic or gabbro high pressure metamorphic rock, mainly composed of garnet and chlorite which are two kinds of minerals. Eclogites record the entire history of subduction zone metamorphism and later exhumation. Due to the crystal habit and the developed joints, the strength of the pyroxene in the matrix is weak, so it is subjected to the main strain during deformation, whereas garnet tends to show only passive rotational deformation. This paper presents some new results in petrology and tectonic geophysics of eclogite block-like and planar eclogite. The massive and facial eclogite rocks contain eclogite facies mineral assemblages, and the peak temperature and pressure conditions are t=450~520°C and P=1.9~2.3 GPa, which are consistent with the adjacent eclogite. Combined with the characteristics of in situ Lu-Hf isotopes, Ce4+/Ce3+ ratios of zircons, relative oxygen fugacity, and absolute oxygen fugacity, it is shown that the oxygen fugacity of the granodiorite porphyry (BL023, BLO31, DB048) of the folio chemical and massive eclogite deposits are all located in MH (magnetite-hematite) buffer zone. Through the calculation results of absolute oxygen fugacity of rock mass, it can be seen that the absolute oxygen fugacity of ore-bearing rock mass is significantly higher than that of non-ore-bearing rock mass. This paper systematically summarizes the research progress of the microscopic and ultrastructural deformation of eclogite minerals in high-pressure metamorphic zones, and discusses the changes of mineral composition, oxygen fugidity, and fabric of eclogite deformation characteristics during the recovery of subduction and reentry.